The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1128/aac.01126-10
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a High-Performance Liquid Chromatography Method for Determination of Cefquinome Concentrations in Sheep Plasma and Its Application to Pharmacokinetic Studies

Abstract: Cefquinome has a broad spectrum of antibacterial activity and was developed especially for use in animals. A simple and sensitive high-performance liquid chromatography (HPLC) method with UV-visible detection for quantification of cefquinome concentrations in sheep plasma was developed and validated. Separation of cefquinome from plasma components was achieved on a Phenomenex Gemini C 18 column (250 mm by 4.6 mm; internal diameter [i.d.], 5 m). The mobile phase consisted of acetonitrile and 0.1% trifluoroaceti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
57
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 18 publications
10
57
3
Order By: Relevance
“…Cefquinome was rapidly and almost completely absorbed (F, 103.04 ± 13.01% vs. 97.56 ± 16.14%, P>0.05) following i.m. injection into two different injection sites, which is consistent with the results in ducks, rabbits, wild boars and sheep [10,14,18,21]. In addition, this result was similar to that in a previous report in piglets after a single i.m.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Cefquinome was rapidly and almost completely absorbed (F, 103.04 ± 13.01% vs. 97.56 ± 16.14%, P>0.05) following i.m. injection into two different injection sites, which is consistent with the results in ducks, rabbits, wild boars and sheep [10,14,18,21]. In addition, this result was similar to that in a previous report in piglets after a single i.m.…”
supporting
confidence: 93%
“…This was similar to the findings for other species, the t 1/2λz and Cl of cefquinome ranged from 0.78 to 1.64 hr and 0.18 to 0.34 l/kg/hr in sheep, rabbits, wild boars and duck indicating the rapid elimination of cefquinome after i.v. injection [10,13,14,18,21]. The V ss of cefquinome in this study was 0.25 ± 0.04 l/kg, which was similar to the reported values of 0.23 l/kg in calves, 0.21 l/kg in rabbits and 0.21 l/kg in horses [10,13,19].…”
supporting
confidence: 89%
“…CFQ could potentially be used for the treatment of many turtle diseases. Pharmacokinetic studies of CFQ have been investigated in salmon (San Martín, Bataglia, Hernández, Quiroz, & Cañon, ), camels (Al‐Taher, ), rabbits (Hwang et al., ), sheep (Tohamy, ; Uney, Altan, & Elmas, ), ducks (Yuan et al., ), ponies (Smiet, Haritova, Heil, Fink‐Gremmels, & Wijnberg, ), cross‐bred wild boars (Liu et al., ), chickens (Xie, Zhang, Wang, & Du, ), pigs (Zhao et al., ), cattle (Shan et al., ), tilapia (Shan et al., ), dogs (Zhang et al., ), buffalo calves (Venkatachalam & Dumka, ), and horses (Uney et al., ). These studies have reported favorable pharmacokinetic features of CFQ, such as good absorption, high bioavailability, and primary elimination via the kidney.…”
Section: Pharmacokinetic Parameters Of Cfq In Red‐eared Sliders (N = mentioning
confidence: 99%
“…The HPLC procedure was based on the method reported by Uney et al . (). Chromatography employed a Gemini™ C18 column (250 mm × 4.6 mm i.d., 5 μm; Phenomenex, Torrance, CA, USA) and a linear gradient of acetonitrile in water with a constant 0.1% trifluoroacetic acid solution at a flow rate of 0.9 mL/min.…”
Section: Methodsmentioning
confidence: 97%